Particle engineering of materials for oral inhalation by dry powder inhalers. I - Particles of sugar excipients (trehalose and raffinose) for protein delivery - HEALY, ANNE; CORRIGAN, OWEN; TAJBER, LIDIA (My University, 2011)
The pulmonary route of delivery offers a potential alternative to parenteral administration of peptides and proteins. Protection of protein structure is essential in both processing and storage of the final formulation. Sugars, such as trehalose and raffinose, have been employed to act as protein stabilisers. Optimisation of the aerodynamic characteristics of microparticles in dry powder inhaler formulations is critical to ensure optimum deposition of the formulation into the respiratory tract. In the present study we examine the adaptation to hydrophilic materials, specifically the disaccharide, trehalose and the trisaccharide, raffinose, of a previously reported spray drying process for producing nanoporous microparticles (NPMPs). We also investigate the feasibility of incorporating a model protein, lysozyme, into these sugar-based NPMPs. While spray drying raffinose or trehalose from aqueous solution or ethanol:water solutions resulted in non-porous microspheres, spray drying from a methanol:n-butyl acetate mixed solvent system resulted in microparticles which appeared to consist of an agglomeration of individual nanoparticles, i.e. nanoporous/nanoparticulate microparticles. NPMPs of trehalose and raffinose were amorphous, with glass transition temperatures (Tgs) that were sufficiently high (124 oC and 120 oC for trehalose and raffinose, respectively) to suggest good physical stability at room temperature and good potential to act as protein carriers and/or stabilisers. NPMPs demonstrated improved aerosolisation properties compared to spray dried non-porous particles. The successful incorporation of lysozyme into these NPMPs at a sugar to protein weight ratio of 1:4 demonstrated the potential of these systems to act as carriers for peptide or protein drugs which could be delivered via the pulmonary route.
PUBLISHED
Keywords: Pharmacology and pharmacy; pulmonary delivery